2022
DOI: 10.3390/medicina58020219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospitalization in an Endocrinology Department on Vaccination Coverage in People Living with Diabetes: A Real-Life Study

Abstract: Background and Objectives: Vaccination coverage is suboptimal in people living with diabetes. The objectives of this study were to determine the impact of hospitalization on vaccination coverage and the variables associated with vaccination during hospital stay. Materials and Methods: This observational study was conducted from May 2019 to December 2019 in the Endocrinology-Nutrition-Diabetes Department of the University Hospital of Montpellier, France. This department encompasses three medical units, two of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Our data indicated a significantly higher uptake of vaccines among patients with DM who have a history of hospitalization compared to those who have never been hospitalized due to DM complications. The results presented in a study by Lohan et al [ 31 ] provide a possible explanation for this finding. The study found an increase in vaccine coverage for influenza, Tdap, and pneumococcal vaccines in patients with DM after being admitted to an endocrinology department.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our data indicated a significantly higher uptake of vaccines among patients with DM who have a history of hospitalization compared to those who have never been hospitalized due to DM complications. The results presented in a study by Lohan et al [ 31 ] provide a possible explanation for this finding. The study found an increase in vaccine coverage for influenza, Tdap, and pneumococcal vaccines in patients with DM after being admitted to an endocrinology department.…”
Section: Discussionmentioning
confidence: 81%
“…Adherence to vaccines was especially noted in the department units that had an inpatient clinical pharmacist involved. This could be attributed to the fact that clinical pharmacists are more attentive to the patient’s medication report and possess skills in educating patients about the importance of vaccinations, thereby facilitating higher vaccine compliance[ 31 ]. This privilege of direct access to physicians, clinical pharmacists, and nurses who can provide information about the vaccines and address the patient’s concerns may explain the increased rate of vaccination in patients with a history of DM-related hospitalizations.…”
Section: Discussionmentioning
confidence: 99%